Padrões cromossômicos e mapeamento de genes ribossomais 18S e 5S em peixes pelágicos Atlânticos - Soares, Rodrigo Xavier (2012)
Cytogenetic studies in fish have been contributed significantly to a better understanding of the marine biodiversity, presenting information related to characterization, evolution and conservation of species e fisheries stocks. Among the marine species which cytogenetic data are less well known pelagic forms are detached, that despite the economic importance and conservation efforts have been suffering great pressure from the artisanal and industrial fisheries. The present work characterized cytogenetically six species of large pelagic fish in the Atlantic, belonging to the Order Perciformes, among them, four species of Scombridae, Thunnus albacares, T. obesus, Scomberomorus brasiliensis and Acanthocybium solandri and two Coryphaenidae, Coryphaena equiselis and C. hippurus using Classical cytogenetic methods as conventional staining, C-banding and Ag-NORs and molecular through staining fluorochromes AT and GC-specific and mapping of ribosomal multigene families, 18S and 5S. The identification of phylogenetic patterns and cytotaxonomic markers between the species and the presence of sex chromosomes in at least one species of Coryphaenidae, are particularly useful in the formulating of phylogenetic hypotheses, as well as comparisons between groups and populations